How migration and its types affect mental health in later life: a cross-sectional study among the older adults in India - Vasim Ahamad; Shamrin Akhtar; Sanjay Kumar Pal; Ram B. Bhagat (BMC Psychiatry)
Abstract Background Migration has extensive consequences on socioeconomic and health status among older adults at the place of destination; various factors in the migration process affect mental health, a prominent social determinant of health. However, no evidence exists of migration and health outcomes among India’s older adults. Thus, the current study investigates the association of individual migration history with depressive symptoms among older Indian adults. Methods This study used information on 64,340 older adults aged 45 and above from the Longitudinal Ageing Study in India (LASI) wave-1, 2017–18. Migration history was calculated, and categories were based on boundary, duration, stream, and age at migration in this study. The depressive symptoms were calculated using both the CES-D and CIDI-SF scores. Using logistic regression models, the association of selected covariates and domains of migration on depressive symptoms was estimated to assess the links between migration and depressive symptoms. Results More than half of the older adults (56.3%) had migrant status in India. The prevalence of depressive symptoms was significantly higher among migrants compared to non-migrants, as measured by both CES-D (30.6% vs. 25.2%) and CIDI-SF (9.3% vs. 6.5%). Multivariate logistic regression revealed that intra-state migrants had significantly higher odds of depression (AOR: 1.08 for CES-D; 1.40 for CIDI-SF) compared to non-migrants. Inter-state migrants also had elevated odds, particularly for CIDI-SF based depression (AOR: 1.38). Among migration streams, rural–to–rural migrants showed the highest odds of depression (AOR: 1.12 for CES-D; 1.39 for CIDI-SF). Duration of migration also influenced mental health: migrants with 25 + years of stay had significantly higher odds (AOR: 1.10 for CES-D; 1.36 for CIDI-SF). Regarding age at migration, individuals who migrated at age 60 or older had the highest odds of depression (AOR: 1.22 for CES-D; 1.42 for CIDI-SF), followed by those who migrated in early life (0–14 years). These findings underscore a strong association between migration history and late-life depression. Conclusions This study’s findings shed light on migration and its association with depression symptoms among older Indians. Older healthcare services should be expanded in breadth while also addressing migration, resulting in considerable improvements in older individuals’ mental health.